PREVALENCE OF POULTRY COCCIDIOSIS IN AND AROUND BAHIR DAR, ETHIOPIA. - Getnet, Tegbar; Alemayhu, Tehetna; Hagos, Yohannes (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
: A cross sectional study was conducted in and around Bahir Dar with the objective of determining prevalence of poultry coccidiosis in local strain and white leghorn breed chicken that are kept under free range and deep litter management systems, respectively. Flotation technique was employed to harvest coccidial oocysts from the sampled chicken faces. Out of a total of 400 chickens examined during the study period 248 (60.6%) were found to be positive for coccidial oocysts. According to breed distribution out of 200 each fecal samples from white leghorn and local strain chickens 69.04 % and 51.7 % were positive, respectively. Regarding, the management system coccidial infection was significantly higher (X2= 12.795; P=0.000) in deep litter management system 145 (69.04%) when compare to free range management system 103(51.7%). Prevalence of coccidiosis according to different age groups indicated that significantly higher prevalence rate of coccidiosis (X2 =28.287; P=0.000) were registered in young chicken when compare to their older counter parts. However, significant variation was not noticed in different sex groups of chickens (X2= 1.367; P=0.242). Generally the present study showed that coccidiosis is an important parasitic disease in the study area and further studies using large sample size should be undertaken so as to get the overall picture of the disease in the area.